Electronic Vapor Product Use and Levels of Physical Activity Among High School Students in Georgia. (5th May 2022) - Rajbhandari-Thapa, Janani; Thapa, Kiran; Li, Yan; Ingels, Justin B.; Shi, Lu; Zhang, Donglan; Shen, Ye; Chiang, Kathryn
Introduction: Using a cross-sectional population-based survey, electronic vapor product (EVP) use was evaluated in relation to physical activity levels among high school students in Georgia. Methods: We used self-reported EVP and cigarette use from the Georgia Student Health Survey 2.0 data from 2018 (N =362 933) and used multi-level multinomial logistic regression models to estimate relative risks of the type of product use relative to no-use by levels of physical activity. Results: Nearly 7% of the students were EVP-only users. The relative risks of being an EVP-only user were 11% and 23% higher for those who were physically active 2-3 days/week and 4-5 days/week, respectively, compared to those who were physically active <=1 day/week. Conclusions: Being physically active was positively associated with EVP use among adolescents. Health promotion education and health policies should be developed as a means of reducing EVP use among adolescents.